Genetic parameter estimates for growth and reproductive trait of sheep for genetic improvement and designing breeding program in Ethiopia: A review - Mekuriaw, S.; Haile, Aynalem (Scientific Research Publishing, Inc., 2014)
Small ruminants in general and sheep in particular are important investments in the highlands of Ethiopia. Genetic and environmental improvements offer an opportunity to increase production from existing animal resources. Development of effective genetic evaluation and improvement programs requires knowledge of the genetic parameters (genetic variance of each trait and covariance among traits) for economically important production traits. Direct heritability estimates for birth weight of Afar sheep (0.13 to 0.38) and BHS (0.20 to 0.58) using univariate analysis; for Horro sheep (0.18 - 0.32) and Menz sheep (0.46) by fitting a multi-trait individual animal model. The weaning weight direct heritability estimates for sheep in Ethiopia, Afar sheep (0.11 - 0.37) and BHS (0.00 - 0.29), Horro sheep (0.10 - 0.26) and Menz sheep (0.48). Fertility, litter size and lamb survival are the components of the overall ewe reproduction traits. It appears that heritability estimates of these traits are rather low and reflect the generally small genetic variance for most reproductive traits. Moreover, litter size has a higher heritability (0.16 - 0.19) than the other components traits like fertility (0.10) and survival rate (0.07 - 0.09) for Awassi sheep breed. Genetic correlations among most pairs of traits were higher than the corresponding phenotypic correlations. Live weights measured at successive ages were highly correlated, ranging from 0.61 to 0.98 for Menz sheep. Genetic correlations were also high between pre-weaning daily gain and weaning weight for Afar and BHS sheep. Except for Blackhead Somali sheep breed which has high genetic correlation between birth weight and weaning weight, Horro, Menz and Afar sheep have high genetic correlation between post-weaning weight traits. This indicates that selection for one trait improves the other trait in those sheep breeds. In order to develop alternative improvement program for sheep breeds in Ethiopia, estimates of genetic parameters for economical growth and reproduction traits should be done by designing experiments since the information on most sheep breed is nonexistence.